Growth performance, health status, gut microbiome, and expression of immune and growth-related genes of rainbow trout (Oncorhynchus mykiss) fed diets with pea protein replacement of fish meal - Yilmaz, Sevdan; Kesbiç, Fevziye Işıl; Acar, Ümi̇t; Kesbiç, Osman Sabri (Elsevier BV, 2024)
The need for fish meal constrains fish farming and significantly impacts sustainability of the aquaculture industry. Hence, it is important to investigate the use of plant-based protein sources in fish diets. The present study was conducted to determine the effects of different levels of fish meal (FM) replacement by pea protein (PP) in a 60-day feeding experiment in rainbow trout, Oncorhynchus mykiss. Effects on growth performance, body composition, hematology, serum biochemistry and immunology, and immune (TNF-α, IL1-ß and Il-8) and growth-related (GH and IGFI) gene expression were investigated. Five experimental diets (45% protein and 20% lipid) differed in replacement level of FM by PP at rates of 0% (control (PP0)), 25% (PP25), 50%(PP50), 75%(PP75) and 100%(PP100). Fish were fed with experimental diets in triplicate twice daily. The best growth performance was obtained in PP0 and PP25 groups. While fat ratios of fish fillets significantly differed (p < 0.05), there was no significant effects on protein ratios (p < 0.05). There was no significant change in the hematological values of fish, except those fed the PP100 diets, which displayed a reduction in eyrthocyte counts, hemoglobin content and hematocrit. As PP supplementation increased fish showed elevated serum glucose, total protein, cholesterol and myeloperoxidase activity and decreased glutamic pyruvic transaminase and alkaline phosphatase activity. Fish fed diets with between 25 and 75% replacement showed a decline in lactic acid bacteria in the gut. Significant increases in expression were observed in the liver of the PP25 fish relative to the 0% control for all immune and growth-related genes except for IL1-ß. These data suggest that up to 25% of FM can be replaced by PP without any adverse effects on rainbow trout.
Keywords: Fish Proteins; Oncorhynchus mykiss; Animals; Animal Feed; Gastrointestinal Microbiome; Pea Proteins; Diet; 2. Zero hunger; 14. Life underwater